Analysis of Image Processing based on Deep Learning: A Review - Firas S. Abdulameer (Genius Publishing Group, 2023)
Image processing involves image analysis and encompasses various subfields, such as medical imaging, medical image mining, web mining, image mining, etc. This article briefly introduces applying the deep learning algorithm to the image segmentation process. Deep learning techniques are crucial in medical image analysis, particularly those used in convolution neural networks (CNN). This article provides an overview of the various applications of deep learning that can be applied to image extraction. In addition, it explains how to retrieve photographs based on their content and how to identify defects in medical photographs. Each application area is introduced briefly, including musculoskeletal, retinal, digital pathology, neuro, abdomen, breast, pulmonary, and cardiac. It would help if you concluded with a current and relevant point, an essential argument regarding outstanding challenges, and guidelines for future research
Keywords: Image Analysi; Image processing; Deep Learning